Pengaruh Health Coaching terhadap Peningkatan Perilaku Pencegahan Tuberkulosis di Kabupaten Tegal - Evi Supriatun; Uswatun Insani (Jurnal Kesehatan Komunitas, 2021)
Tuberculosis is the deadliest infectious disease in the world. The most prevalence is in Asia and Africa. The study aimed to find out the effect of health coaching on tuberculosis prevention behaviors for patients diagnosed with the disease. The research used Quasy Experiment pre-posttest with control group on 68 respondents consisted of treatment and control group. It was started by having validity and reliability test of research questionnaires, providing health coaching as one of the health promotion strategies in nursing divided into 4 sessions, performing univariate test to describe the research variables and bivariate test; independent t-test and pair t-test. The results independent t test showed that mean of tuberculosis behavior of intervention group is higher more than 8,88 control group. The effect of health coaching was a significant difference in tuberculosis prevention behaviors with p value = 0,000.The coaching presented to patients with tuberculosis included physical prevention behaviors and improving body endurance by getting stress management. To sum up, health coaching can increase tuberculosis prevention behaviors significantly for patients with tuberculosis who are being treated.